Jesse Jackson for President Rally at Warnor's Theatre - Watkins, Howard::::::::: (1984)
Jesse Jackson at microphone with standing ovation; Barbara Gaines, Pauline Kimber, ?, Les Kimber, Ben Benavidez all applauding